Effects of postweaning management system and breed on growth and carcass traits - K.M. Andries; R.R. Schalles; D.E. Franke; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1996)
Data from 5 years of a long-term, rotational, crossbreeding project were used to calculate heritabilities and correlations and to make breed comparisons for growth rate and carcass traits in two different postweaning management systems. The traits studied were weight per day of age, hot carcass weight, ribeye area, marbling score, and days of age at slaughter. One group was placed on full feed after weaning. A second group underwent a backgrounding phase for 7 months at Louisiana State University before being placed on feed at KSU. The breeds involved were Angus, Brahman, Charolais, Hereford, Simmental, and Gelbvieh. Differences in heritabilities between management systems were generally small, indicating similar genetic expression across management systems. Genetic correlations also were high except for marbling score, which indicates some difference in genetic expression between management systems for this trait. Some changes in rank of breeds occurred between management systems, but they generally were not significant.
Keywords: Cattlemen' s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Breeds; Management; Carcass traits; Genetics; Growth